POLA GANDA (PROGRAM PELATIHAN GAMOLAN ANAK DAERAH) SEBAGAI UPAYA TERWUJUDNYA GENERASI BERWAWASAN BUDAYA DI SDN 2 SULUSUBAN LAMPUNG TENGAH - dkk, Hasyimkan, (Jurnal Warna, 2018)
The activity devotion of Pola Ganda (Training Program Gamolan Anak Daerah) is motivated from the idea that there should be introduction and development of Gamolan instrument in SD Negeri 2 Sulusuban. This is because Gamolan which is one of the pride of the people of Lampung shows quite a fact of irony, because in fact most of the people of Lampung, especially in the Village Sulusuban Central Lampung regency does not know the instrument. With the hope that through this service can straighten the wrong understanding in society as well as efforts to conserve, protection, development and utilization of Gamolan, and aims to streamline Pola Ganda in realizing the generation of cultural insight as well as being able to consider and encourage the government to better preserve local culture. Devotion of Pola Ganda is done by giving learning about history and making of Gamolan as well as intensive training some of Gamolan beats which collaborated with Rebana and Gong to students who are members of Mulei-Mekhanai Gamolan community and teacher board of SD Negeri 2 Sulusuban. The training process uses the Rolling Group method and fun learning.